Inovasi Layanan di UPT Perpustakaan Universitas Pasundan - Hilman Firmansyah (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2016)
The development of information and communication technologies have a positive impact and significant for the development of libraries. It will be realized when librarians wisely supported stakeholders to capture and utilize information and communication technologies in the management of an innovation in the Library. Innovation does not only provide a solution to the saturation in the works but also, raise the ratings of webometrics college